Productivity and the Welfare of Nations - Basu, Susanto; Pascali, Luigi; Schiantarelli, Fabio; Serven, Luis (World Bank, Washington, DC, 2012)
This paper shows that the welfare of a country's representative consumer can be measured using just two variables: current and future total factor productivity and the capital stock per capita. These variables suffice to calculate welfare changes within a country, as well as welfare differences across countries. The result holds regardless of the type of production technology and the degree of market competition. It applies to open economies as well, if total factor productivity is constructed using domestic absorption, instead of gross domestic product, as the measure of output. It also requires that total factor productivity be constructed with prices and quantities as perceived by consumers, not firms. Thus, factor shares need to be calculated using after-tax wages and rental rates and they will typically sum to less than one. These results are used to calculate welfare gaps and growth rates in a sample of developed countries with high-quality total factor productivity and capital data. Under realistic scenarios, the U.K. and Spain had the highest growth rates of welfare during the sample period 1985-2005, but the U.S. had the highest level of welfare.